Work from home: Measuring satisfaction between work-life balance and work stress during the COVID-19 pandemic in Indonesia - Dodi W. Irawanto; Khusnul Rofida Novianti; Kenny Roz (Economies, 2021)
Coronavirus (COVID-19), which hit in early 2020, changed the way people live and work, and affected industries and organizations all over the world. Many organizations have begun to deliver a new way of working to adapt to these shifts effectively using teleworking or a work from home policy. The purpose of this study was to fill the gaps by investigating several potential predictors of job satisfaction during working from home from the impact of COVID-19 such as work-life balance and work stress. Using a quantitative approach, 472 workers who were forced to work from home all over Indonesia participated, and the responses were analyzed using Smart-PLS software. The study revealed that working from home, work-life balance, and work stress have a significant effect, both directly and indirectly, on job satisfaction. Working from home as a new pace of work can sustain job satisfaction as the current working atmosphere for Indonesian workers. In response to the collectivist setting, working from home can be a positive sign that needs to be paid attention to for the organization.
Keywords: 330; COVID-19; job satisfaction; teleworking; work from home; work stress; work-life balance